The most complete political machine ever known the North's Union Leagues in the American Civil War - Taylor, Paul 1959- (Civil War in the North, 2018)
"This book in the Civil War in the North series examines the Union League movement and its influence on the Northern home front in the Civil War."...Provided by publisher